PROMOTING RESPONSIBILITY THROUGH THE MATHEMATICS CAPITA SELECTA COURSE WITH RECIPROCAL TEACHING STRATEGY BASED ON IGNATIAN PEDAGOGY - Dominikus Arif Budi Prasetyo (Sanata Dharma University Yogyakarta, 2018)
During the learning, mathematics education students are taught about various mathematical theories. The material is useful when they become teachers or mathematicians. Mathematics Capita Selecta is one of the elective courses of mathematics education program that aims to help students able to make a study related to the latest mathematics topic. The purpose of this research is to describe the students responsibility on the Mathematics Capita Selecta Course with Reciprocal Teaching Strategy based on Ignatian Pedagogy. Implementation of this learning model includes the process of extracting context, experience, reflection, evaluation and action in hope of optimizing the competence, compassion and conscience of students. The competence focus helps students to solve the assignment in the Mathematics Capita Selecta Course well. Whereas in terms of conscience, the design is expected to help students hone responsible attitude. And in terms of compassion, the design is expected to appreciate diversity. Data analysis method used is descriptive qualitative-quantitative. The subjects of this study are students who take the Mathematics Capita Selecta Course in the second semester of 2016-2017. In this course, lecturer use Reciprocal Teaching Strategy, where students in groups are given the task of discussing a mathematics article, presenting in class, and producing new articles. The results of this study is the reciprocal teaching strategy helps students to complete their responsibilities, so that as many as 6 groups can present their articles at the National Conference at Muhammadiyah University Purworejo. This strategy requires students to understand the selected articles and discuss in the classroom. In the aspect of responsibility attitude including very high category. On the student reflection note, almost all students claimed to always strive to serve and be trustworthy when given responsibility. When you have a responsibility, there is no need to force things to remain trustworthy. Students are increasingly willing and able to complete their responsibilities both personally and in groups shown by indicators working together, completing tasks and communicating very high.DOI: https://doi.org/10.24071/ijiet.2018.020209